Food portions and consumer vulnerability: qualitative insights from older consumers. Issue 3 (10th June 2019) - Ford, Nicholas; Trott, Paul; Simms, Christopher
Abstract : Purpose: The purpose of this paper is to explore older people's food consumption experiences. Specifically, the paper seeks to provide understanding on the influence of food intake on consumer vulnerability and how this manifests within people's lives. Design/methodology/approach: The study adopts an interpretive, exploratory approach, using in-depth interviews with 20 older consumers in the UK. Thematic analysis is conducted, establishing patterns and contradictions with the data. Findings: The findings demonstrate how biological, psychological and social age-related changes can contribute to reduced food intake in later life. The loss of control over one's consumption experiences as a result of inappropriate portion sizes acts as a source of both immediate and future vulnerability. Resultant food wastage can serve as an immediate reminder of negative associates with ageing, while the accumulative effect of sustained under-consumption contributes to increased frailty. As a result, consumer vulnerability can pervade other contexts of an individual's life. Practical implications: The research reveals opportunities for firms to use packaging development to reduce experiences of consumer vulnerability through reduced apportionment of packaged food products. However, this needs to be considered within a multi-demographic marketplace. Originality/value: This paper contributes to literature by providing a unique lens with which to understand consumer vulnerability. The findings offer a developmental perspective on the experience of consumer vulnerability, revealing the stages of proximate, immediate, intermediate and ultimate vulnerability. This perspective has the potential to offer more detailed, nuanced insights into vulnerability in other contexts beyond food consumption.